A Guide to Citrus Nutritional Deficiency and Toxicity Identification - Stephen H. Futch; P.H. Tucker (EDIS)
This document explains the importance of accurately identifying symptoms of various disorders in citrus trees, which can affect their health, vigor, and productivity. It emphasizes the challenges in distinguishing nutritional deficiencies or toxicities from other issues, such as herbicide or fungicide damage and physiological stress. Nutritional disorders, particularly those involving micronutrients like zinc, manganese, and iron, can manifest differently on different parts of the tree and may not always match descriptions in publications. The text advises seeking expert advice when symptoms are unclear to avoid costly and potentially harmful remedial actions. First published Oct. 2000.